Microparticles That Form Immune Complexes as Modulatory Structures in Autoimmune Responses - Catalina Burbano; Mauricio Rojas; Gloria Vásquez; Diana Castaño (Hindawi Limited, 2015)
Microparticles (MPs) are induced during apoptosis, cell activation, and even "spontaneous" release. Initially MPs were considered to be inert cellular products with no biological function. However, an extensive research and functional characterization have shown that the molecular composition and the effects of MPs depend upon the cellular background and the mechanism inducing them. They possess a wide spectrum of biological effects on intercellular communication by transferring different molecules able to modulate other cells. MPs interact with their target cells through different mechanisms: membrane fusion, macropinocytosis, and receptor-mediated endocytosis. However, when MPs remain in the extracellular milieu, they undergo modifications such as citrullination, glycosylation, and partial proteolysis, among others, becoming a source of neoantigens. In rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE), reports indicated elevated levels of MPs with different composition, content, and effects compared with those isolated from healthy individuals. MPs can also form immune complexes amplifying the proinflammatory response and tissue damage. Their early detection and characterization could facilitate an appropriate diagnosis optimizing the pharmacological strategies, in different diseases including cancer, infection, and autoimmunity. This review focuses on the current knowledge about MPs and their involvement in the immunopathogenesis of SLE and RA.